Tooth whitening in conventional orthodontic patients: a systematic review - Hernández-Viana, Stefanía (2022)
This systematic review aimed to identify and critically evaluate the available evidence of the appropriate moment to perform tooth whitening in conventional orthodontic patients. A systematic review in MEDLINE and SciELO databases from inception to February 2021 was carried out by two independent reviewers. Randomized clinical trials, non-randomized clinical trials, case-control, cohort, cross-sectional, case-series and reviews that focused on the application of tooth whitening during or after orthodontic treatment were considered for inclusion. The primary outcome was defined as tooth whitening during/after orthodontic treatment. The secondary outcome included the time in days after bracket debonding in which tooth whitening was performed. Risk of bias analysis was performed for each study and the findings were synthesized in a narrative summary. A total of 4 randomized clinical trials, 1 non-randomized clinical trial and 3 reviews were included in the qualitative synthesis. One study performed tooth whitening during, and three studies after orthodontic treatment. One study compared tooth whitening during and after orthodontic treatment. The time after which tooth whitening was applied following bracket debonding ranged from 7 to 90 days with a mean value of 40.2 days. All studies reported satisfactory improvements in tooth color shade during or after orthodontic treatment independent of the protocol. Low quality evidence suggests that the appropriate moment to perform tooth whitening in conventional orthodontic patients is after brackets removal with a waiting period of at least 30 days. There is not adequate evidence to support tooth whitening during conventional orthodontic treatment.